Analisis Hukum Terhadap Wanprestasi pada Perjanjian Kerjasama Pengelolaan Kebun Kelapa Sawit (Studi: PT. Tepian Gayor Langkat) - Tanjung, Putri Marwin; Ramadhan, Muhammad Citra; Siregar, Fitri Yanni Dewi (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This study aims to analyze the implementation of the oil palm plantation management cooperation agreement at PT. The edge of Gayor Langkat, identifies the default that occurred, and evaluates legal remedies and legal consequences arising from the violation. This study uses a normative juridical approach with qualitative descriptive analysis based on literature studies and interviews. The data was analyzed to identify defaults, legal remedies, and consequences in the agreement of PT. The banks of Gayor Langkat. The results of the study show that the implementation of the cooperation agreement between PT. The banks of Gayor Langkat and Darmawan Armiadi were declared in default due to violations of Articles 3, 4, and 8 related to written approvals, financial statements, and profit sharing. The Second Party failed to fulfill its obligations, causing the First Party to lose Rp. 138,726,000. After legal remedies such as reprimands, summonses, and lawsuits, the court ruled on default, canceled the agreement, and sentenced the Second Party to pay damages of Rp200,000,000. This case emphasizes the importance of a strong agreement, strict supervision, and compliance to prevent losses and ensure fairness.